2020
DOI: 10.1002/jcsm.12636
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis and degradation regulate translational capacity during muscle disuse and reloading

Abstract: Background Translational capacity (i.e. ribosomal mass) is a key determinant of protein synthesis and has been associated with skeletal muscle hypertrophy. The role of translational capacity in muscle atrophy and regrowth from disuse is largely unknown. Therefore, we investigated the effect of muscle disuse and reloading on translational capacity in middle‐aged men (Study 1) and in rats (Study 2). Methods In Study 1, 28 male participants (age 50.03 ± 3.54 years) underwent 2 weeks of knee immobilization followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 68 publications
6
36
0
Order By: Relevance
“…Changes in ribosomal synthesis (ribosomal biogenesis) have been shown to correlate with changes in muscle protein synthesis during loading 15,16,34 . In recent studies, we have shown that atrophy caused by disuse is associated with decreases in myofibrillar protein synthesis, increases in myofibrillar protein degradation and dramatically upregulated ribosomal degradation without changes to ribosome biogenesis 16,33 . In the current investigation, we observe that a correlation between ribosome biogenesis and myofibrillar protein synthesis exists in the sham limb (during normal loading conditions), but not in the denervated limb.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Changes in ribosomal synthesis (ribosomal biogenesis) have been shown to correlate with changes in muscle protein synthesis during loading 15,16,34 . In recent studies, we have shown that atrophy caused by disuse is associated with decreases in myofibrillar protein synthesis, increases in myofibrillar protein degradation and dramatically upregulated ribosomal degradation without changes to ribosome biogenesis 16,33 . In the current investigation, we observe that a correlation between ribosome biogenesis and myofibrillar protein synthesis exists in the sham limb (during normal loading conditions), but not in the denervated limb.…”
Section: Discussionsupporting
confidence: 47%
“…The decline in translational efficiency and capacity caused by a period of muscle disuse may be a therapeutic target to regain muscle in the period after disuse 33 . Changes in ribosomal synthesis (ribosomal biogenesis) have been shown to correlate with changes in muscle protein synthesis during loading 15,16,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In the skeletal muscle, it is widely known that inactivity causes disuse atrophy 21-23 and that reactivation improves atrophy. 24-26 In contrast, there are no previous studies on its treatment and recovery, and the treatment and recovery processes for disuse atrophy of the articular cartilage are unclear. Owing to the absence of blood vessels and dependence on nutrition from the synovial fluid, it is traditionally believed that the articular cartilage has a poor repair capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomes are central to conversion of mRNA to protein 41 and an increase in mRNA coding for ribosomal RNAs have been observed during hypertrophy of rat cardiomyocytes, 42 plantaris muscle in rat and vastus lateralis in human. 43 Reduction in methylation of genomic regions of ribosomal DNA is associated with increased biogenesis of ribosomal RNA. 44 Furthermore, many of the genes associated with DMC are associated with growth or muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant change in methylation for these genes due to choline was hypomethylation. Ribosomes are central to conversion of mRNA to protein 41 and an increase in mRNA coding for ribosomal RNAs have been observed during hypertrophy of rat cardiomyocytes, 42 plantaris muscle in rat and vastus lateralis in human 43 . Reduction in methylation of genomic regions of ribosomal DNA is associated with increased biogenesis of ribosomal RNA 44 .…”
Section: Discussionmentioning
confidence: 99%